Soil Radioactivity and Radiological Risks Exposure to Inhabitants near Coastal Region of Ado- Odo Ota, Ogun State, Nigeria - Maxwell, Omeje (International Journal of Psychosocial Rehabilitation, 2020)
Background radiation assessment was carried out in and around near coastal areas of Ado- Odo Ota in Ogun State Nigeria to ascertain the soil potential health risks exposure to the inhabitants of the zone. Ninety eight stations with a spacing of 12 m were measured for the radioactivity levels from the naturally occurring radionuclide (238U, 232Th and 40K) as well as the corresponding dose rates using highly sensitive portable gamma ray spectrometer (Super-Spec RS 125). The results showed that the measured value of 238U varied from 44 to 79 Bq/kg. For 232Th, it ranges between 37 and 121 Bq/kg respectively. The 40K measured values ranged between 312 and 672 Bq/kg. Radiological parameters such as radium equivalent, internal hazard and external hazard assessments were estimated. The estimated values ranged from 143 to 351 Bq/kg, 0.76 to 0.95 and 0.51 to 0.84 for radium equivalent, internal hazard and external hazard respectively. The measured values of gamma dose-rates ranged between 76 and 181 nGyh-1. The measured radionuclides and estimated radiological parameters were compared with international reference value and were found to be within the recommended values except those results from the stations adjacent to the production companies where over 60 % of the population densely occupied. The annual effective dose and cancer fatal risks exposure to inhabitants were found to be within the permissible level except 9 stations truncated towards the dumpsite area.These higher values of exposure risks that twice exceeded the permissible levels according to UNSCEAR, 2000 may be attributed to the industrial waste materials from the major Companies in the area. However, this study suggests that the authority should compel the companies to adequately channel both the wastes and drainage systems towards the unoccupied area of about 1000 m away from the zone as well as proper yearly Environmental impact assessment for the safety of the general public.